Efektywność inwestycyjna OFE w latach 1999-2005 - Stańko, Dariusz (Investment performance of Polish Open Pension Funds (OFEs) during 1999-2005, 2006)
This paper is an abridged version of [8, chapters 4-5] investigating the investment performance of Polish open pension funds (so-called OFEs) during the period: 1 June 1999 - 28 February 2005. The monthly data is used to calculate the continuously compounded rates of returns of OFEs, stock market, bond market, and T-bills. The OFEs rates of returns are net of management fees but do not account for up-front charges. Using the Sharpe ratios and the unconditional Jensen market model, the performance of OFEs was investigated against the V20 (author’s stock index based on WIG20 allowing for the dividends’ effect), GOPL and AA (author’s asset allocation index) benchmarks. The article finds statistically significant positive abnormal returns for the pension industry and for some of the individual OFEs. The FI test confirms the industry ability to beat the indexes; however the F2 test does not give grounds to the conclusion that some individual pension funds had consistently outperformed the others.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 500-508